Smoking Cessation Behavior Among Madurese Adolescents: The Role of Social Capital and the Theory of Planned Behavior - Sujono Riyadi; Marmi Marmi; Shalahuddin Al Madury; Muhammad Farid (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: The high prevalence of smoking among Madurese adolescents reflects a complex public health challenge. This study aims to analyze the influence of social capital and elements of the Theory of Planned Behavior on smoking cessation intentions among Madurese adolescents within their local cultural context. Methods: A cross-sectional path analysis was conducted with 200 adolescents aged 15–19 years in Sumenep, Madura, using a structured questionnaire to measure attitudes, subjective norms, perceived behavioral control, and smoking cessation intention. Social capital was assessed through three dimensions: trust, social networks, and reciprocity norms, within the context of adolescents' relationships with family, peers, and the broader community. Results: The findings reveal that strong social support from family and peers significantly influences adolescents' intentions to quit smoking, strengthening the effectiveness of Theory of Planned Behavior (TPB) factors in driving positive behavioral change. Path analysis showed that the intention to quit smoking had a direct and significant effect on actual smoking cessation behavior (? = 1.56; p < 0.001). Attitudes, subjective norms, and perceived behavioral control demonstrated indirect effects through intention. Adolescents with high perceived behavioral control and positive attitudes toward quitting were more likely to succeed in cessation efforts. Conclusion: These results emphasize the importance of social capital in anti-smoking interventions, especially in culturally cohesive societies such as Madura. Future interventions should leverage community and family-based support systems to enhance smoking cessation efforts among adolescents.